Blood Alcohol Concentrations in Suicide and Motor Vehicle Crash Decedents Ages 18 to 54. (1st March 2016) - Conner, Kenneth R.; Lathrop, Sarah; Caetano, Raul; Silenzio, Vincent; Nolte, Kurt B.
Abstract : Background: Using postmortem data, we examined the hypotheses that high (and very high) blood alcohol concentrations (BACs) are more common among motor vehicle crash decedents (MVCs) than among suicide decedents, whereas low alcohol levels are more common among suicides. Methods: We examined BAC in 224 suicide decedents and 166 MVCs ages 18 to 54 in the state of New Mexico in 2012. Comparisons between the groups were made based on differing BAC levels using 0.080 g/dl categories including low (0.001 to 0.079 g/dl), high (0.080 to 0.159 g/dl), and very high BAC (≥0.160 g/dl), and based on 0.100 g/dl categories including low (0.001 to 0.099 g/dl), high (0.100 to 0.199 g/dl), and very high BAC (≥0.200 g/dl), with these groups compared with a no‐alcohol reference (0.000 g/dl) in separate analyses. Multivariate logistic regressions compared suicides with MVCs that adjusted for age, sex, and race/ethnicity. Results: Support for the hypothesis that suicides are more likely to have a low BAC level was supported in the analysis using the 0.100 g/dl categorizations. Neither analysis supported the hypothesis that MVCs are more likely to have high (or very high) BACs compared with suicides. Among both injury groups with positive BACs, low BACs were least common. Conclusions: Low BAC levels may be more likely to be observed among suicides compared with MVCs, a possible reflection of the more varied role that alcohol plays in suicide compared with MVC. Nonetheless, high (and very high) BAC is the predominant scenario in both suicides and MVCs with positive BAC. Abstract : The study examined postmortem blood alcohol concentrations (BACs) in 224 suicide decedents and 166 motor vehicle collision decedents (MVCs) ages 18 to 54 in the state of New Mexico in 2012. Results show that high (and very high) BAC levels are typical in both types of deaths and also suggest that suicides may be more likely to have a low BAC level (<0.100 g/dl), potentially attributable to a role of drinking apart from intoxication effects in some suicides.